Proteomes and ubiquitylomes reveal the regulation mechanism of cold tolerance mediated by OsGRF4 in rice - Zhang, Li; Huang, Renyan; Mao, Donghai; Zeng, Jia; Fang, Pengpeng; He, Qiang; Shu, Fu; Deng, Huafeng; Zhang, Wuhan; Sun, Pingyong (Frontiers in Plant Science, 2025)
Low temperature is one of the major abiotic stresses that severely restrict the development of rice. It has been demonstrated previously that OsGRF4 enhances cold tolerance in rice, the molecular mechanism of which remains unknown. This study employed a combination of proteome and ubiquitylome approaches to analyze OsGRF4 mediated chilling between the overexpression line (OX) and wild type (CK). Proteome results showed that 6,157 proteins were identified and 5,045 proteins were quantified after 24-h cold treatment. A total of 59 proteins were upregulated and 63 proteins were downregulated in the OX24 vs. OX0 group; 27 proteins were upregulated and 34 proteins were downregulated in OX24 vs. CK24. Finally, 3,789 ubiquitination modification sites were located on 1,846 proteins, of which 2,695 sites of 1,376 proteins contained quantitative information. However, 178 sites in 131 proteins were quantified as upregulated and 92 sites in 72 proteins were quantified as downregulated differentially ubiquitin-modified proteins (DUMPs) in OX24 vs. OX0. To the contrary, 82 sites in 71 proteins were identified as upregulated and 13 sites in 12 proteins were identified as downregulated DUMPs in CK24 vs. OX24. The results suggested that global ubiquitination levels increase during cold tolerance in rice. In total, 76 differentially abundant proteins and 101 DUMPs were co-localized within 50 cold or stress tolerance Quantitative Trait Locis (QTLs). The combined analysis of proteomics and ubiquitination omics found that five proteins demonstrated opposing changes in protein and ubiquitination; the protein Q6ZH84 (Os02g0593700) was an upregulated differentially abundant protein (DAP) but was a downregulated DUMP in OX24 vs. OX0, which is a homologous gene of NBR1 that regulated cold tolerance. Os02g0593700 should upregulate protein expression by reducing ubiquitination modification, thus affecting cold tolerance. The enrichment pathway shows that OsGRF4 plays an important role in rice cold tolerance by ubiquitination through glutathione metabolism and arachidonic acid metabolism. The research provides a new perspective on the molecular mechanism of cold tolerance regulated by OsGRF4.